Implementing a tiered approach to bioanalytical method validation for large-molecule ligand-binding assay methods in pharmacokinetic assessments. (September 2017) - Watson, Rebecca G; Clements-Egan, Adrienne; Schantz, Allen; Ware, Mark; Wu, Bonnie; Yang, Tong-Yuan; Shankar, Gopi; Marini, Joseph C
Bioanalytical methods must enable the delivery of data that meet sound, scientifically justified, fit-for-purpose criteria. At early phases of biotherapeutic drug development, suitable criteria of a ligand-binding assay could be met for pharmacokinetic (PK) in-study sample testing without a full validation defined by regulatory guidelines. To ensure fit-for-purpose methods support PK testing through all phases of biotherapeutic development, three tiers of method validation – regulatory, scientific and research validations – are proposed. The three-tiered framework for method validation outlines the differences in the parameters that should be assessed, the acceptance criteria that may be applied, and the documentation necessary at each level. The criteria for selecting the appropriate application of each of these PK method validation workflows are discussed.